XL-MIMO with Near-Field Spatial Non-Stationarities: Low-Complexity Detector Design - Zhi, Kangda; Pan, Cunhua; Ren, Hong; Chai, Kok Keong; Wang, Cheng Xiang; Schober, Robert; You, Xiaohu (Proceedings - IEEE Global Communications Conference, GLOBECOM, 2023)
In this work, we propose low-complexity designs for XL-MIMO in the near-field with spatial non-stationarities. We first introduce a notion of visibility region (VR) and propose a VR detection algorithm. Then, we exploit the acquired VR information to design a low-complexity detection scheme for XL-MIMO systems. To further reduce the complexity, we propose a graph theory-based user partition algorithm, relying on the VR overlap ratio between different users. Then, partial zero-forcing (PZF) is utilized to eliminate only the interference from users allocated to the same group, which further reduces computational complexity in matrix inversion. Numerical results confirm the effectiveness of the proposed algorithms which approach the performance of conventional whole array (WA)-based designs but with much lower complexity.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Extremely-large-scale MIMO; near-field communications; spatial non-stationarities; visibility region